The Panorama of Artificial Intelligence – Development or Advancement? - Ondřej Roubal; Kateryna Narusevych (Communication Today, 2025)
The objective of this study is to identify and describe the main milestones in the development of artificial intelligence in the form of a chronological overview of its historical development. This study also seeks to present an argument that challenges the stereotypically and uncritically accepted thesis that draws no distinction between the concepts of development and advancement as they apply to artificial intelligence. Development is a mechanism following a process of leaps forward, without a goal, without criteria based on values or morals. Progress is an ambivalent phenomenon, the practical outcome and result of a specific developmental phase of interacting social, technological, economic, and cultural factors. A historical understanding of the context that gave rise to the development of key concepts of artificial intelligence technologies is the foundation for further possible scientific analysis and qualified predictions of the transformation of society. The phenomenon of artificial intelligence is distinctive for its ambivalent nature. On one hand, it contributes to the prosperity of society, increases efficiency, accelerates performance, and makes a range of human activities easier and more precise. On the other hand, artificial intelligence generates unseen social risks, transforms the function of cultural patterns, and breaks social norms, raising philosophical, ethical, moral, and legislative questions. This review study can serve as a starting point for further study and research analyses to identify the main trends in the technological development of artificial intelligence in the context of questions of advancement in social, cultural, political, economic, ethical, or legislative transformations of society.